2023
DOI: 10.1002/fsn3.3385
|View full text |Cite
|
Sign up to set email alerts
|

Functional stirred yogurt manufactured using co‐microencapsulated or free forms of grape pomace and flaxseed oil as bioactive ingredients: Physicochemical, antioxidant, rheological, microstructural, and sensory properties

Abstract: Functional stirred yogurt samples were manufactured with combinations of grape pomace (GP) and flaxseed oil (FO) in microencapsulated or free forms (2% w/w) and quality characteristics of yogurts were investigated during 21 days of storage. The incorporation of GP and FO in microencapsulated or free forms caused a significant decrease in pH, syneresis, and a significant increase in acidity, water holding capacity, and viscosity of stirred yogurt (p < .05). While stirred yogurt containing GP and FO in free form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Consequently, BM containing BP exhibits substantial antioxidant activity, positioning it as a novel dairy product with notable health benefits. Our research agrees with those of previous reports, which described that the addition of berry industry by-products contained higher radical scavenging activity due to the higher amount of phenolic compounds [ 31 , 37 ]. Also, similar findings were presented by Najgebauer-Lejko and Sady [ 42 ] where BM flavored with strawberry and rhubarb exhibited higher radical scavenging activity (0.88 mmol of TE/kg) compared with the control sample.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, BM containing BP exhibits substantial antioxidant activity, positioning it as a novel dairy product with notable health benefits. Our research agrees with those of previous reports, which described that the addition of berry industry by-products contained higher radical scavenging activity due to the higher amount of phenolic compounds [ 31 , 37 ]. Also, similar findings were presented by Najgebauer-Lejko and Sady [ 42 ] where BM flavored with strawberry and rhubarb exhibited higher radical scavenging activity (0.88 mmol of TE/kg) compared with the control sample.…”
Section: Resultssupporting
confidence: 93%
“…TPC without BP ranged from 4.9 ± 0.9 to 6.2 ± 0.04 mg GAE/g during the storage period ( Figure 3 ), attributed to naturally occurring phenolic compounds in cultured BM-based fermented drinks. Similarly, Saberi et al [ 37 ] observed significantly higher total phenolic content values in fortified yogurts with grape pomace and flaxseed oil compared to a control yogurt during storage. Similar tendencies were observed in the study of Starkute et al [ 31 ], where the total phenolic content and antioxidant activity significantly increased in enriched samples, demonstrating the potential of raspberry, blueberry, and elderberry industry by-products for enhancing the nutritional and functional properties of unripened cow milk curd cheese.…”
Section: Resultsmentioning
confidence: 87%
“…In both yoghurt samples, a broad band is observed in the range from approximately 3000 to 3500 cm −1 , which relates to the vibration of the hydroxyl group. In both samples, bands were observed at 2920 cm −1 (symmetric stretching vibration of CH 2 -groups of fatty acids) and at 2854 cm −1 (asymmetric stretching vibration of CH 2groups in membrane lipids) [54,55]. We also observe characteristic bands for the first-and second-order amide groups at 1630 and 1530 cm −1 , respectively.…”
Section: Ftir-atrmentioning
confidence: 66%
“…In the food industry, grape pomace and its constituents have traditionally been utilized in powdered form as a nutritional supplement in various foods due to their abundance in phenols, dietary fiber, and anthocyanins [44]. Through a comprehensive review of existing literature, grape pomace and its constituents have been extensively studied for their potential incorporation into a variety of foods including bread [45][46][47][48], confectionery [49][50][51], cookies [52][53][54], yogurt [55][56][57], ice cream [58][59][60], pasta [61][62][63], noodles [64], fruit candies [65][66][67], beverages [68][69][70] and more. Consequently, incorporating grape pomace into foods presents a two-sided outcome, yielding both advantageous and disadvantageous effects on the final products.…”
Section: Journal Of Engineering Sciencementioning
confidence: 99%